DI BALIK PEMIKIRAN TOKOH PENDIDIKAN ISLAM INDONESIA: MODERASI, KEMANUSIAAN, DAN KEARIFAN LOKAL UNTUK PENDIDIKAN DASAR - Rahmi, Yen Happy; Hidayat, Adi; Zadri, Muhammad; Silvia, Mira; M, Iswantir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the thoughts of Indonesian Islamic education figures related to moderation, humanity, and local wisdom in strengthening Islamic education at the elementary level. The background of this study is based on the increasing challenges of intolerance, moral degradation, and the weakening of cultural values in educational practices. Therefore, the study aims to analyze the educational thoughts of KH. Hasyim Asy’ari, KH. Ahmad Dahlan, Azyumardi Azra, and Quraish Shihab and their relevance to the development of moderate and contextual Islamic education in Indonesia. This research employed a qualitative approach using the library research method by examining books, journals, scientific articles, and other relevant references related to Islamic educational thought. The findings indicate that the thoughts of these figures emphasize the importance of character education, religious moderation, tolerance, social awareness, and the integration of local wisdom in educational practices. KH. Hasyim Asy’ari emphasized education based on moral values and character, KH. Ahmad Dahlan promoted the integration of religious and modern sciences, Azyumardi Azra highlighted moderate Islam and intellectual networks, while Quraish Shihab focused on the concept of wasathiyah in understanding Islamic teachings. These ideas are highly relevant to strengthening Islamic education at the elementary level in order to develop students who are religious, tolerant, socially aware, and capable of living harmoniously in a multicultural society.